The little mermaid [videorecording (DVD)] (Walt Disney signature collection., 2019)
Ariel is a beautiful mermaid princess with an even more beautiful voice, who just happens to be enthralled with the human world so much that she disobeys her father to visit the surface. When she rescues a handsome prince from drowning, the sea-witch Ursula recognizes an opportunity to tempt the naive girl and overthrow the kingdom at the same time.